Demographic characteristics of female luxe-bargain clothing shoppers: an acquisition-transaction utility approach - Erasmus, Alet C. (Aletta Catharina) (University of Pretoria, 2019)
Dissertation (MConsumer Science)--University of Pretoria, 2018.